2022
DOI: 10.21037/atm-21-4361
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of hetrombopag in patients with chronic immune thrombocytopenia: a single-arm, open-label, multi-center phase 1 study

Abstract: Background: Thrombopoietin receptor agonists (TPO-RAs) are promising therapeutic strategy for patients with immune thrombocytopenia (ITP). We conducted this phase 1 trial (NCT02614846) to evaluate the preliminary efficacy and safety of hetrombopag (a TPO-RA) in patients with ITP.Methods: Patients with ITP who had an insufficient response or had progressed on at least one standard treatment for ITP were given hetrombopag orally at an initial dose of 5 mg once daily for up to 6 weeks.The primary endpoint was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…However, theoretically, they also increase the risk of thrombosis ( 7 ). Both single-arm and controlled trials have reported cases of thrombosis treated with TPO-RAs with an incidence rate of 2-6% ( 8 , 10 , 25 ). A previous systematic review compared the risks of thrombotic events between TPO-RA and non-TPO-RA treatments ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, theoretically, they also increase the risk of thrombosis ( 7 ). Both single-arm and controlled trials have reported cases of thrombosis treated with TPO-RAs with an incidence rate of 2-6% ( 8 , 10 , 25 ). A previous systematic review compared the risks of thrombotic events between TPO-RA and non-TPO-RA treatments ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to meet this selection demand, it is particularly important to fnd new TPO-RA preparations. Hetrombopag, the new generation of TPO-RA, is a smallmolecule [21], oral, nonpeptide thrombopoietin receptor agonist and is currently the only brand-new originator TPO-RA approved for immunologic thrombocytopenic purpura (ITP) and aplastic anemia (SAA) in China. Compared with eltrombopag, hetrombopag has a stronger signaling pathway activation efect, an earlier onset of action, and a longer duration of action and naturally leads to better clinical efcacy at the same dose.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally modified Eltrombopag to improve efficacy and reduce adverse effects, under the name of Getrombopag, is being investigated in clinical trials only in adult ITP patients in China (Mei et al 2022).…”
Section: )mentioning
confidence: 99%